Spatio-temporal patterns of an anthrax outbreak in white-tailed deer, Odocoileus virginanus, and associated genetic diversity of Bacillus anthracis. Issue 1 (December 2015) - Mullins, Jocelyn; Ert, Matthew; Hadfield, Ted; Nikolich, Mikeljon; Hugh-Jones, Martin; Blackburn, Jason
Abstract Background Anthrax, a soil-borne zoonosis caused by the bacteriumBacillus anthracis, is enzootic in areas of North America with frequent outbreaks in west Texas. Despite a long history of study, pathogen transmission during natural outbreaks remains poorly understood. Here we combined case-level spatio-temporal analysis and high resolution genotyping to investigate anthrax transmission dynamics. Carcass locations from a single white-tailed deer, Odocoileus virginanus, outbreak were analyzed for spatial clustering usingK -function analysis and directionality with trend surface analysis and the direction test. Results The directionalities were compared to results of high resolution genotyping. The results of the spatial clustering analyses, combined with deer movement data, suggest anthrax transmission events occur within limited spatial areas, with carcass locations occurring within the activity space of adjacent cases. The directionality of the outbreak paralleled adjacent dry river beds. Isolates from the outbreak were represented by a single genotype based on multiple locus variable number tandem repeat analysis (MLVA); four sub-genotypes were identified using single nucleotide repeat (SNR) analysis. Conclusions Areas of high transmission agreed spatially with areas of higher SNR genetic diversity; however, SNRs did not provide clear evidence of linear transmission. Overlap of case home ranges provides spatial and temporal support for localized transmission, which may include the role of necrophagous or hematophagous flies in outbreaks in this region. These results emphasize the need for active surveillance and prompt cleanup of anthrax carcasses to control anthrax both during outbreaks and between seasons.